Effect of Profitability, Liquidity, Solvency and Firm Size on Going Concern Opinion - Santalina Yani Surbakti; Mikha Vivia Crisia; Tetty Tiurma Uli Sipahatur (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study intends to assess and analyze the effect of Profitability, Liquidity, Solvency, and Company Size on Going Concern Audit Opinions on Manufacturing Companies on the Indonesia Stock Exchange for the 2017-2019 period. A sample of 315 companies were selected using purposive sampling. The data used is secondary data using descriptive statistical data analysis and logistic regression. Based on the results of the study, it shows that: 1) Profitability, Liquidity, Firm Size have no significant effect on going concern audit opinion. 2) Solvency has an effect on going concern audit opinion. 3) Profitability, Liquidity, Solvency and Company Size affect going concern audit opinion simultaneously because the significant value is 0.019, which means the value is <0.05.